Lab-on-a-chip approaches for space-biology research - Wan Salim, Wan Wardatul Amani; Park, Joon Hyeong; Ul Haque, Aeraj; Porterfield, David Marshall (Bentham Science Publishers, 2013)
Lab-on-a-chip (LOC) systems with electrochemical sensing capability can provide real-time physiological measurements in spaceflight environments. They are easily miniaturized and integrated with existing space hardware systems. To reduce crew time during spaceflight research, the systems can be made autonomous and simple to use. Research and development of electrochemical-sensing LOC systems are still in progress for fundamental space-biology research in microgravity. Ion-selective electrodes as electrochemical sensors are miniaturized in an all-solid-state format for easier packaging and handling. The design, fabrication, and application of these sensors are discussed, with examples from those developed at the Physiological Sensing Facility (PSF) at Purdue University. The objective of this paper is not to provide an exhaustive review of current LOC systems, but to describe research developments made for the purpose of conducting physiological measurements in microgravity with examples of patents that support space missions.